HUMOR AND SATIRE IN W. SHAKESPEARE’S COMEDIES - Aktamova Zarnigor Yahyo qizi; Xalilova Mohinurbonu Jalolovna; Xalmuratova Fariza Elmurad qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT. This article is written mainly through information about Shakespeare's comedies. Especially, in this article, we wrote about humor and satire and their purpose of application in his comedies.